Awareness of the Benefits of Strategic Planning For Educational Institutions - Rachmad, Ferizal (InJEBA : International Journal of Economics, Business and Accounting, 2023)
This article aims to determine the benefits of strategic planning for Islamic educational institutions. The method used is a literature review, by collecting various supporting article references from national journals. The results of this study explain, if strategic planning can be made and implemented correctly and supported by leadership commitment, then strategic planning can provide benefits for Islamic educational institutions, including: (1) Strategic planning can strengthen the "critical mass" into a team that compact, because it is directed to adhere to basic values, main systems and common goals, (2) Strategic planning can help to optimize the performance of Islamic educational institutions, (3) Strategic planning can help leaders to always focus attention and adhere to a framework for overall improvement efforts continuous, (4) Strategic planning provides guidelines for daily decision making, and (5) Strategic planning always makes it easy to measure the organization's progress in achieving its goals of improving quality and productivity. The benefits of educational strategic planning are things that need to be considered to create quality Islamic educationh